2017
DOI: 10.1111/tbed.12741
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of duck hepatitis a virus types 1 and 3 in China, 2010-2015

Abstract: Duck hepatitis A virus (DHAV) is the most common aetiologic agent of duck virus hepatitis (DVH), causing substantial economic losses in the duck industry worldwide. In China, officially approved DHAV-1 live-attenuated vaccines have been used widely to vaccinate breeder ducks since 2013. However, following the reports of DVH outbreaks, it has become necessary to assess the epidemiological situation of this virus in China. We conducted molecular epidemiological analyses of 32 DHAV field isolates while analysing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 21 publications
1
47
0
Order By: Relevance
“…Recently, genetic analysis and molecular characterization of Egyptian DHAV-1 isolates have been described based on VP1 gene sequencing (16). The analyses showed that Egyptian DHAV-1 isolates have been clustered into genetic group 4 with virulent Chinese strains (17). Lately, the Egyptian DHAV-1 isolates were classified into three subgroups (A, B, and C) under genetic group 4 based on their geographical distribution (18).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, genetic analysis and molecular characterization of Egyptian DHAV-1 isolates have been described based on VP1 gene sequencing (16). The analyses showed that Egyptian DHAV-1 isolates have been clustered into genetic group 4 with virulent Chinese strains (17). Lately, the Egyptian DHAV-1 isolates were classified into three subgroups (A, B, and C) under genetic group 4 based on their geographical distribution (18).…”
Section: Introductionmentioning
confidence: 99%
“…In DHAV infection, it has been reported that activation of the toll-like receptor 7 (TLR7) pathway is involved in the immune response and viral clearance [34]. To date, some epidemiological, pathogenic and immunological mechanisms of DHAV have been reported [35][36][37]. It is likely that different picornaviruses adopt various strategies to interfere with cellular resources.…”
Section: Introductionmentioning
confidence: 99%
“…Duck hepatitis A virus type 1 (DHAV-1), a member of the genus Avihepatovirus with characteristics of the family Picornaviridae ( 1 8 ), was first reported in Long Island, New York in 1945. DHAV-1 poses a serious threat to the duck industry worldwide ( 9 , 10 ). There was recently an outbreak of DHAV-1 infection in Japan, and the nucleotide sequences of outbreak PCR products exhibited 96% identity with the HB02 strain of DHAV-1, which was isolated in China ( 11 ).…”
Section: Introductionmentioning
confidence: 99%